Developing agency through good work: longitudinal effects of job autonomy and skill utilization on locus of control - Griffin, Mark A; Parker, Sharon K.; Wu, Chia-Huei (My University, 2015)
An internal locus of control has benefits for individuals across multiple life domains. Nevertheless, whether it is possible to enhance an individual's internal locus of control has rarely been considered. The authors propose that the presence of job autonomy and skill utilization in work can enhance internal locus of control, both directly and indirectly via job satisfaction. Three waves of data over a four-year period from the Household, Income and Labour Dynamics in Australia Survey (N = 3045) were analyzed. Results showed that job autonomy directly shaped internal locus of control over time, as did job satisfaction. Skill utilization did not play a role in terms of affecting locus of control, and the indirect effects of both job autonomy and skill utilization via job satisfaction were weak. This study suggests the importance of job autonomy in promoting the development of an employee's internal locus of control.
Keywords: Beliefs and Values -- Personality; Employment; Identity; Labour market; Beliefs and Values; Employment; Personality; Employment and unemployment; Identity